PERANCANGAN APLIKASI INFORMASI PENJUALAN BERBASIS WEBSITE DENGAN PENERAPAN METODE ALGORITMA APRIORI (STUDI KASUS : ZAY CELL SAWANGAN DEPOK): (STUDI KASUS : ZAY CELL SAWANGAN DEPOK - Munaldi; Wau, Zefani (CV. Multi Kreasi Media, 2023)
The purpose of this study is to determine data associations or commonly called combinations that are useful as a reference for optimizing stock inventory and recommendations for promotional activities that can be carried out at the Zay Cellular counter. this emphasizes more on the number of product items that are often purchased as a calculation of sales patterns that will be made at the Zay Cellular counter. The result of creating a data processing information system is that it makes it easier to process transaction data as the main reference for optimizing the supply of goods to be sold. The method used by the researcher is appropriate because the results of the data that have been processed in combination produce data on product items that are frequently purchased and can make it easier for owners to optimize the supply of goods to be sold appropriately to customers. Keywoard : Data Mining, Apriori Algorithm, Association, Stock Inventory